(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
This paper presents an account of the performance “Chuva de Direitos” (“Rain of rights”) which I performed twice in public spaces in Rio de Janeiro in 2018. The work is a reenactment of the performance “Chuva de Dinheiro” ("Rain of Money"), created and performed by Márcia X. in co-authorship with Ana Cavalcanti in 1983 and 1985. As an introduction, I briefly contextualize the artists’ original work, as well as the notion of reenactment underlying the tribute I carried out more than three decades later.